REFLECTION OF THE TRAGEDY OF THE EPOCH AND ITS INFLUENCE ON HUMAN DESTINIES IN FICTION (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
The article deals with the coverage in the works of Uzbek writers of the problems of moral decline of society in the transition period, and the influence of this factor on human destinies.